Exploring Effects of Interventions on Aspiring Entrepreneurs’ Psychological Capital, Creative Self-Efficacy, and Well-Being - Savickaitė-Kazlauskė Evelina; Bendaravičienė Rita (Organizacijų Vadyba: Sisteminiai Tyrimai, 2023)
This paper examines the effectiveness of the pilot emotional intelligence programme with individual coaching interventions in enhancing the psychological capital, creative self-efficacy, well-being, and life satisfaction of entrepreneurship students. The study, involving 16 students from an entrepreneurship academy, shows that these interventions have a positive impact on these psychological aspects, both immediately after the sessions and in the long term. The results indicate a strong interconnection between psychological capital and its components and well-being, and to a lesser extent, with creative self-efficacy.